E-Modul Interaktif Berbasis Sole pada Materi Peluang - Syahidah, Marwa; Maifalinda Fatra; Dindin Sobiruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop an interactive e-module based on the Self-Organized Learning Environment (SOLE) model on chance material to facilitate mathematical problem solving skills of junior high school students. The method used is research and development with the PLOMP model which goes through three stages: initial research, development, and assessment. Of the nine test items, seven were declared valid based on the Content Validity Ratio (CVR) analysis. The e-module development results have been validated by material experts and media experts with an average score of 88.52%, which indicates that the e-module is very feasible to use. The results of the problem solving ability test reached a score of 85.54, exceeding the school's Minimum Completion Criteria (KKM). Students also gave positive responses to the e-module from the aspects of material, appearance, and interest. This shows that e-modules are not only valid and practical, but also effective in facilitating mathematical problem solving skills. In conclusion, this SOLE-based interactive e-module is effective as a digital learning media to support students' mathematical problem solving skills and can be used as a supplement to teaching materials for mathematics teachers. Keywords: Interactive E-Module, Mathematics, Problem Solving, SOLE